Gossip: Struktur, Peran dan Praktek - Dwi Wulandari (Endogami: Jurnal Ilmiah Kajian Antropologi, 2023)
This  theoretical study aims at finding out the structure, role and how people do gossiping within different culture. As in conversation, gossip is also performed by both males and females in many different cultures.  It is understood that the nature of gossip done by females is different compared to those done by males, although many argue that gossiping is identical with females’ language behaviors. Gossip is mostly performed in the form f negative evaluation. Nevertheless, gossip can also be neutral, in that it only talks about facts, or it can even be  in the form of positive evaluation that is gossiping the goodness of the third party. Gossip has its own nature and structure that differentiate it with the other type of conversation. Gossip also has its social functions; as social control, as capital symbol in social transaction , and to construct and to keep social identity. Gossiping behavior is influenced by local norm and culture. With that reason, although in general there are similar nature and role of gossip throughout different cultures, in reality there are also differences on gossiping behavior.